Los montículos Oquendo durante el Periodo Intermedio Temprano en el valle bajo del Chillón, costa central del Perú - Acero Shapiama, Erick Ernesto (2021)
The excavations realized by the Archeological Program of the Federico Villarreal University, were focused in the Oquendo area, lower valley of the Chillon river, central coast of Peru at the end of 90´s; it convered excavations in the mounds: 4, 5 and 6; its stratums contained white on red pottery, organic materials, combustion activities (pit) and others; all of them associated a temporal occupations. This data permitted us to make comparisons with certain sites of the Lurin valley, Chancay and Rimac rivers (Patterson 1966a, 1966b, y 2014; Córdova 1999; Goldhausen 2014; Acero 2015 and others), which they kept into the culture dynamic problematic and the white on red pottery presence, its used mean popularity with differentes nuances, since the perspective focused in the Chillon valley during the Early Intermediate Period.